Training effects on subsistence entrepreneurs' hope and goal attainment. Issue 7 (12th August 2019) - Barrios, Andres; Reficco, Ezequiel; Taborda, Rodrigo
Abstract : Purpose: The purpose of this paper is to explore the extent to which hope and perceived goal attainment can be developed in subsistence entrepreneurs through the right training tools. Design/methodology/approach: A longitudinal study of a subsistence entrepreneurship training program in three Central American countries was carried out. Participants were divided on the basis of their exposure to training (yes, no), and of the type of training received (none, business plan, business model). The authors carried out three assessments (just before the program, six months and one year after the program) of participants' business goals and their hope of attaining them. Information was analyzed using linear regression. Findings: Participants exposed to training reported significant increases in perceived goal attainment and in their hope levels. Training based on the business plan affected hope agency in the short term, as predicted by the logic of causation theory. Training based on the business canvas affected hope pathways, as predicted by the logic of effectuation theory. Research limitations/implications: Given the data collection process (a non-random sample and selection of participants), the findings are not generalizable without stringent procedures and further replication. Practical implications: If hope is a reliable predictor of goal attainment, it should be promoted and measured. Given the limited means of gathering data and making reliable projections that most entrepreneurs endure, the business canvas' contribution to entrepreneurs' "emotional equipment" ceteris paribus should be more valuable for subsistence entrepreneurs. Originality/value: This is the first study comparing the short- and long-term effects of two entrepreneurial learning devices on entrepreneurs' hope and business goal attainment.